Effects of Lemon balm essential oil application on atopic dermatitis-like immune alterations in mice - Jian-Rong Zhou; Eri Fujiwara; Yuuki Nakamura; Mihoko N. Nakasima; Kazumi Yokomizo (International Journal of Phytomedicine, 2015)
Lemon balm oil has been used as anti-inflammation agent, but there has been no scientific study to date on the possible effects of Lemon balm oil on alleviating atopic dermatitis. BALB/c mice were sensitized with 2, 4-dinitrochlorobenzene for atopic dermatitis induction. Thereafter, Lemon balm oil was applied on the dorsal skin for 4 weeks. Scratching behavior was measured. Blood and spleen were collected for measuring IgE and cytokine, respectively. Serum IgE levels were significantly lowered in 3% Lemon balm oil application group after 3-week application. The Lemon balm oil application showed a significantly lower spleenocyte interleukin-10 level and an increasing tendency in Interferon- level compared with that of saline application. Scratching frequency of the Lemon balm oil application group had a lower tendency than the control groups. This study may demonstrate Lemon balm oil’s immunoregulatory potential for alleviating atopic dermatitis through influencing of Th2 / Th1 cell activation.